Family values and psychological distress among adolescents. Is there any association? a comparison study in Malaysia - Musa, Ramli; Shafie, Nurfatin Shahera; Zulkifli, Nurul Afiqah; Kamaruzaman, Nur Atira; Al-Ani, Ali Sabri Radeef (University of Messina, Italy, 2019)
Background: Adolescence is a critical transition phase in the life of an individual to be independent and to mould their own identity. Family dynamic is the most influential factor in adolescent mental health. Objectives. This research aimed to analyse the differences of family values, psychological distress and its associated finadolescents living in a long-term residential care as compared to adolescents in an ordinary school. Method: A cross-sectional study was carried out with 150 respondents using clustered random sampling. The Asian Family Characteristics Scale was used to assess the family values. The Depression, Anxiety and Stress Scale was used to measure the mental state of the respondents. Results: Children in long-term residential care showed significantly lower family values in all domains and higher in levels of stress, anxiety, depression. Findings show that there is significant association between psychological distress and family values. Conclusion: Family dynamic has a strong ramification to behavioural and psychological aspects of adolescents. Preventive measures and policy maker should be advocated in order to minimize psychological problems among adolescence in this country.